Faktor-Faktor yang Berpengaruh terhadap Kejadian Leptospirosis (Studi Kasus Kontrol di Kabupaten Pati) - Marek Samekto; Suharyo Hadisaputro; Mateus Sakundarno Adi; Suhartono Suhartono; Bagoes Widjanarko (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
Background: Limitations of data regarding risk factors that affect the incidence of leptospirosis in endemic areas make leptospirosis control in Leptospirosis endemic areas not effective. Therefore, a study is needed to determine the factors that influence the occurrence of Leptospirosis in an area.Methods: An observational analytic was conducted with case-control study design. The population in this study were all patients found at the Hospital in Pati Regency who showed clinical symptoms of Leptospirosis (fever >38 oC, severe headache, calf muscle pain, red/yellowish red eyes) and had a laboratory examination with Leptotek Lateral Flow and recorded on medical records. The sample in this study were 44 cases and 44 controls with consecutive sampling technique. Data were analyzed by chi-square and logistic regression.Results: Variables that influence the occurrence of leptospirosis are the characteristic of the non-ratproof house with OR = 3.14 (95% CI = 1.16-8.47), the existence of rats in and around the house with OR = 3.66 (95% CI = 1.67-12.28), the behavior of walking barefoot during outdoor activities with OR = 1.57 (95% CI = 1.31-10.28).Conclusion: Several factors that have been proven to have an effect on the occurrence of leptospirosis are the characteristic of the non-ratproof house, the existence of rats in and around the house and the behavior of walking barefoot during outdoor activities.